Immunotherapy with radiotherapy in urological malignancies. Issue 6 (November 2016) - Mehta, Shaveta; Illidge, Tim; Choudhury, Ananya
Abstract : Purpose of review: Radiotherapy has the potential to augment the host's immune response to cancer. Urological malignancies are highly immunogenic and the combination of radiotherapy and immunotherapy shows promise. In this review, we discuss the effects of radiotherapy on the cancer immune system and highlight the rationale for using the combined approach in prostate, urothelial and renal cancers. Current clinical studies are summarized emphasising the synergistic effects of the combination and the possibility of improved clinical outcomes. Recent findings: Local and abscopal effects have been observed in different urological cancers when using a combined approach. Large fraction size is associated with an increased immune response. Multiple radiotherapy/immunotherapy combinations are being studied in several clinical trials although no combination has yet been introduced in to standard practice. Summary: Although our knowledge of immunomodulation by radiotherapy has improved significantly in recent times, there remain several unanswered questions regarding how to best use the combination in clinical practice. Ongoing trials will provide further insight into complex mechanisms governing radiotherapy-immunotherapy interactions, with potential to improve clinical outcomes.